Fundamentals of Advanced Accounting, 4th Edition - Schaefer Thomas (Mc Graw-Hill, 2010)
Fundamentals of Advanced Accounting, 4/e is ideal for those schools wanting to cover 12 chapters in their advanced accounting course. This brief yet concise text allows students to think critically about accounting, just as they will do preparing for the CPA exam. With this text, students gain a well-balanced appreciation of the Accounting profession. The text continues to show the development of financial reporting as a product of intense and considered debate that continues today and into the future as it originates from Hoyle’s big text Advanced Accounting.